Urbanization and urban systems in India - "Ramachandran, R." (Delhi Oxford University Press, 1989)
This substantive and original contribution to the study of urbanization in India critically analyses the strengths and weaknesses of the Indian urban system and provides new insights into contemporary urban problems. The author's perspective of urban development in India interrelates the geographical dimension with historical and socio-economic aspects. The book focuses on the processes of urbanization and the nature of interdependence among urban centres and between urban centres and their hinterlands. The approach is at the macro level. The first chapter provides an overview of studies of urbanization in India, and a detailed chapter on the history of urbanization follows. These provide the necessary background to the chapter on urbanization processes. The locational aspects of urbanization are covered in the next five chapters which discuss the problem of defining an urban place, spatial patterns of urbanization, classification of cities, theories of settlement location and the analysis of settlement systems. The relationships between a city and its surrounding area are then studied at two levels - the larger area of city dominance and the city fringe area. Finally, the author examines the fundamental issues involved in framing a national urbanization policy, and expresses the hope that the development of smaller cities and towns may provide some relief from the problems of overcrowding and unplanned growth.
Keywords: Urbanization -India